System dynamics simulation model to assess impacts of personnel factors on delayed software projects - Farshchi, Mostafa (2011)
According to the latest survey‘s reports, the software project‘s failure is considerably high despite the advancement in the field of software project management. Many projects were being announced to be completed beyond their planned schedule. Delivery of a software project beyond its schedule cannot be tolerated. The delay may result in the loss of a market opportunity and can be a cause of failure to a dependent project . Schedule slippage could even incur a much higher cost than the cost of the project itself. Therefore, software project managers may take any possible arrangement to ensure that the project completed on time, such as adding new manpower to the project. Adding new manpower to an ongoing delayed software project may cause negative impacts to the team productivity due to assimilation time, training overhead and communication overhead. Consequently, project managers have difficulties to make the decision whether to add new members to his team or not. Therefore, this research attempts to investigate how software project managers can minimize the negative influence of adding new manpower to delayed software projects. More specifically, this research aims to examine whether a significant schedule improvement can be achieved with proper consideration of the new manpower capabilities, skills and experience. A system dynamics approach has been employed for in-depth investigation of the issue. Accordingly, a System Dynamics Simulation Model is proposed to simulate the dynamic behaviour of the project progress when new members are added to the project. Some principal attributes of the model such as assimilation time, communication overhead and training overhead have been adopted from the previously developed system dynamics models. The COCOMO II personnel factors productivity multipliers are also employed to represent various personnel factors in the proposed model. The proposed model was verified and validated by experiments with two cases: a literature case and an industry case. The results of the experiments indicate that significant schedule improvement of a late project can be achieved if people with certain levels of capabilities and experience are added to the project. Furthermore, the findings of this research demonstrates that software project managers can take the advantages of employing system dynamics approach for detailed trade-off analysis of adding new manpower to a project.